How common is remission in rheumatoid factor-positive juvenile idiopathic arthritis patients? The multicenter Pediatric Rheumatology Academy (PeRA) research group experience - Semanur Ozdel; Hafize Emine Sönmez; Şengül Çağlayan; Özlem Akgün; Tuncay Aydın; Özge Baba; İlknur Bağrul; Gülçin Otar Yener; Kübra Öztürk; Ferhat Demir; Deniz Gezgin Yıldırım; Şerife Gül Karadağ; et al. (BMC, 2023)
Abstract Objective Rheumatoid factor (RF)-positive polyarthritis is the least common type of juvenile idiopathic arthritis (JIA). Functional disability in RF-positive polyarthritis patients is much more severe than in patients with other subtypes; but data on this subtype alone is limited. This study aimed to analyze clinical features, long-term follow-up, treatment response, and remission status in a large multicenter cohort of RF-positive polyarthritis patients. Methods This retrospective study included RF-positive polyarthritis patients that were followed up for ≥ 6 months between 2017 and 2022 by the Pediatric Rheumatology Academy (PeRA)-Research Group (RG). Data on patient demographics, clinical and laboratory characteristics were obtained from medical charts. JIA treatments and duration of treatment were also recorded. The patients were divided into 2 groups based on methotrexate (MTX) response, as follows: group 1: MTX responsive, group 2: MTX unresponsive. Clinical and laboratory findings were compared between the 2 groups. Results The study included 56 (45 female and 11 male) patients. The median age at onset of RF-positive polyarthritis was 13.2 years [(interquartile range) (IQR): 9.0-15.0 years] and the median duration of follow-up was 41.5 months (IQR: 19.5-75.7 months). Symmetrical arthritis affecting the metacarpophalangeal and proximal interphalangeal joints of the hands was commonly observed. Subcutaneous MTX was the preferred initial treatment; however, it was ineffective in 39 (69.6%) of the patients. Of 25 patients followed for 24 months, 56% still had active disease at 24 months. Conclusion During 2 years of treatment, 44% of RF-positive polyarthritis patients have inactive disease, and they should be considered as a distinct and important clinical entity requiring aggressive and early treatment.